European Union - Eap - Moldova. Reflections on the Perspectives of the Emergence of Transnational Justice on Anti-Corruption and Anti-Fraud Dimension - Andrei PÂNTEA; Serghei PÂNTEA (Eastern European Journal of Regional Studies, 2019)
This research analyzes comprehensively the perspectives of the emergence of European transnational justice on the anti-corruption and anti-fraud dimension. Following the analysis of jurisprudence, the normative framework, trends and historical evolution, both in the member states of the European Union, in their relation with the institutions of the Union, as well as the relation of the Union with the third states, it is considered that the involvement, or the interest of supranational institutions, as well as of the Union as a whole, for the defense of its financial interests is inevitable. The involvement through the financing of the various projects, the allocation of different funds or, as a generic category, their management, will be closely monitored. When elaborating on the findings and conclusions, the emphasis was placed on analysis and synthesis, forecasting method, and in some aspects, it was attempted to extrapolate, or to extend in the future, the dynamics and expected results, with emphasis on investigations in third countries, within the meaning of the conventional framework. The theoretical and scientific support of the paper is extensive, applying the logical, historical, comparative and systemic methods of research.